2005
DOI: 10.1021/je049552d
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of p-Aminophenol in Sulfuric Acid + Water from (286.15 to 362.80) K

Abstract: Using a laser monitoring observation technique, the solubilities of p-aminophenol in sulfuric acid + water have been determined experimentally from 286.15 K to 362.80 K. The experimental data were correlated with the modified Apelblat equation. The calculated results showed good agreement with the experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…respectively. The temperature dependence of isonicotinic acid solubility at fixed solvent composition is described by the modified Apelblat equation [8][9][10] ln…”
Section: Resultsmentioning
confidence: 99%
“…respectively. The temperature dependence of isonicotinic acid solubility at fixed solvent composition is described by the modified Apelblat equation [8][9][10] ln…”
Section: Resultsmentioning
confidence: 99%
“…By using the data shown in Table 1, T-x curves for p-aminophenol + sulfuric acid + water + alcohols system [i.e., the p-aminophenol + sulfuric acid + water + (methanol, ethanol, and 1-propanol, respectively) systems as shown in Figure 2, p-aminophenol + sulfuric acid + water + (1-propanol, 1,2-propanediol and glycerin respectively) systems as shown in Figure 3, and p-aminophenol + sulfuric acid + water + (1-propanol and 2-propanol respectively) systems as shown in Figure 4] were plotted. For comparison, the T-x curves for p-aminophenol + sulfuric acid + water based on the literature values 14 were also drawn in every figure . From Figure 2 it can be found that, for the mixed solvent systems containing normal monohydric alcohol, the solubility of p-aminophenol increases with the increase of the carbon atom numbers of the alcohols at constant temperature. From Figure 3 it can be known that, for the mixed solvent systems containing 1-propanol, 1,2-propanediol, and glycerin, respectively, which all contain three-carbon atoms, the solubility of p-aminophenol in the mixed solvents decrease with the increase of hydroxyl group numbers of the alcohols at constant temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the associations, the interaction intensity between A-B is far weaker than that between A-A or B-B, so the solubility of p-aminophenol in water is very low. 14 With the adding of sulfuric acid in the system, a stronger interaction between the alkaline -NH 2 group in p-aminophenol molecule and the H + in the solution occurs, which makes the solubility of p-aminophenol in the mixed solvent increase obviously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations